Effects of centrally acting analgesics on spinal segmental reflexes and wind‐up. (2nd December 2014) - Mazo, I.; Roza, C.; Zamanillo, D.; Merlos, M.; Vela, J.M.; Lopez‐Garcia, J.A.
Abstract Background The spinal cord is a prime site of action for analgesia. Here we characterize the effects of established analgesics on segmental spinal reflexes. The aim of the study was to look for the pattern of action or signature of analgesic effects on these reflexes. Methods We used a spinal cord in vitro preparation of neonate mice to record ventral root responses to dorsal root stimulation. Pregabalin, clonidine, morphine and duloxetine and an experimental sigma‐1 receptor antagonist (S1RA) were applied to the preparation in a cumulative concentration protocol. Drug effects on the wind‐up produced by repetitive stimulation of C‐fibres and on responses to single A‐ and C‐fibre intensity stimuli were analysed. Results All compounds produced a concentration‐dependent inhibition of total spikes elicited by repetitive stimulation. Concentrations producing ∼50% reduction in this parameter were (in μM) clonidine (0.01), morphine (0.1), pregabalin (1), duloxetine (10) and S1RA (30). At these concentrations clonidine, pregabalin and S1RA had significant effects on the wind‐up index and little depressant effects on responses to single stimuli. Morphine and duloxetine did not depress wind‐up index and showed large effects on responses to single stimuli. None of the compounds had strong effects on the amplitude of the non‐nociceptive monosynaptic reflex. Conclusions morphine and duloxetine had general depressant effects on spinal reflexes, whereas the effects of clonidine, pregabalin and S1RA appeared to be restricted to signals originated by strong repetitive activation of C‐fibres. Results are discussed in the context of reported behavioural effects of the compounds studied.